An Examination of Nutritional Approaches and Stress Levels in Athletes: Nutritional approach and stress - Tutkun, Erkut (Progress in Nutrition, 2020)
For athletes, nutrition is very important not only for sporting success but also with regard to health. The aim of this study is to determine nutritional approaches and stress levels in athletes. A total of 420 athletes aged 17-24, studying at Ondokuz Mayıs University, took part in the study. The participants’ BMI was calculated from their age, height and body weight, and a nutritional approach test questionnaire and perceived stress scale were applied. For the statistical evaluation, student t-test, one-way variance analysis and LSD tests were used. The average ages of the students were 22.13 for females and 22.85 for males. BMIs were determined as 22.00 kg/m2 for females and 24.15 kg/m2 for males. Nutrition scores were calculated as 16.49 for females and 18.06 for males. In the nutrition questionnaire, according to the gender of the students evaluated, no statistically significant difference was determined among ages (p>0.05), whereas statistically significant differences were determined among heights, body weights and BMI values (p<0.001). While the differences between athletes’ nutrition scores were not found to be statistically significant according to gender (p>0.05), the total score distributions in the nutritional approach test were found to be statistically significant according to BMI (p<0.05). 87.7% of the athletes believed that they had the correct body weight for the sport that they played. In the stress category, the nutrition score was 21.4 in the group with stress scores of 20 and below, while the nutrition score decreased to 16.48 in the group with stress scores between 21 and 30. The nutrition score in the group with stress scores over 30 was determined as 13.85. It was established that nutrition scores differed significantly according to stress category (p<0.05). In conclusion, it was found that both male and female athletes’ nutritional approaches were at a good level, and that as stress levels decreased, nutrition scores increased. It can be said that the athletes’ nutritional knowledge and behaviours were at adequate levels. It is recommended that further information is given with regard to nutrition, health and stress reduction